Hak-hak anak dalam undang-undang perlindungan anak no. 23 tahun 2002 untuk memperoleh pendidikan dalam perspektif islam - Amrullah, Muhlasin, Prof. Dr. Bambang Sumardjoko, H. Muhtarom, S.H., M.H (2014)
Children are the future generation who should be protected. Indonesia protects the children by showing it in Undang-Undang Perlindungan Anak No. 23/2002. The children protection in Indonesia should consider the children's rights in Islam considering most of Indonesian is Moslem. The objective of the research is to describe comprehensively the children' rights to obtain education in UU No. 23/2002 and also to describe the children's right to obtain education in UU No. 23/2002 viewed by Islamic point of view. The research is literary research, which analyzes the children's right to obtain education written in Undang-Undang Perlindungan Anak No. 23/2002 viewed by the perspective of Islam. The research uses descriptive analysis method. The primary sources used in the research is book of Undang-Undang Perlindungan Anak No. 23/2002, hadist (traditional collection of stories relating words or deeds of Muhammad the chief source of guidance for understanding religious questions) and the verses from Qur'an dealing with the children's rights. While the secondary sources used in the research is journals dealing with the children's right to obtain education. Based on the research, it can be concluded that; the children's rights to obtain education written in Undang-Undang No. 23/2002 are a) The children's right to live, grow, be protected and participate properly, b) The right to obtain education and learning, c) The right to obtain inclusion education for disabled children, d) The right to obtain a special education for them who have a great ability, e) The right to express their arguments, f) The right to receive, look for, and give information. According to the analysis of the children's right to obtain education written in Undang-Undang No. 23/2002 viewed by the perspective of Islam, it is clearly stated that the children's right is protected by Qur'an and Sunnah. Islam considers education as the children's right, therefore the children have the right to grow and obtain a good education as it is stated in the objective of Islamic education. a) The right to grow and develop based on the dignity, b) The right to grow and develop, and having the education as reflected in Islam's objective, c) The right for those disable without discrimination, d) The right for those potential children by using the principal of children's development ability,e) The right to argue and being responded by using the responsible education's basic as portrayed in Islamic principals, f) The rights to accepting, seeking, and giving information in order to create the system of education by educator as reflected in Islamic education. Unfortunately, education based on UU No. 23/2002 seems to see it formally, and then it is also dichotomous, it's not integrated between general and religious education.